Excess selenium intake is associated with microalbuminuria in female but not in male among adults with obesity: Results from NHANES 2009–2018 - Zhang, Jia-wei; Lin, Yi; Liu, Yue-min; Wang, Min-min; Gong, Jian-guang; Shen, Xiao-gang; Shen, Quan-quan; Lin, Bo; Su, Wei-er; Gao, Yuan-cheng; Yuan, Chen-yi; Pan, Zhi-hui; et al. (Frontiers in Nutrition, 2023)
Introduction Selenium is a critical trace element with antioxidant activities that has been related to the preservation of kidney function. Few studies, however, have looked at the effects of excess selenium on kidneys. The purpose of the present study was performed to investigate the relationship between dietary selenium intake and the prevalence of microalbuminuria in American adults with obesity. Methods A total of 8,547 participants with obesity in the National Health and Nutrition Examination Survey (NHANES) with the age of 19 years or older were included in the present study. Multivariable regression and subgroup analyses were performed to examine the association between dietary selenium and microalbuminuria in the two genders, separately. A selenium intake above the median was defined as high selenium intake. Results Dietary selenium intake was significantly higher in men compared to women (139.49 μg/day vs. 101.06 μg/day; P < 0.0001). Among female participants, the prevalence of microalbuminuria was significantly higher in participants with a high selenium intake compared with those without a high selenium intake (13.82 vs. 9.96%; P = 0.008), whereas this difference did not exist in male participants (10.79 vs. 11.97%; P = 0.40). Dietary selenium is not significantly correlated with microalbuminuria (P = 0.68) in the male population, whereas each 1 μg/day of increase in selenium consumption was independently associated with a 6h higher risk of microalbuminuria (OR = 1.006; 95% CI, 1.001–1.011, P = 0.01) in females. Conclusion According to our research, excessive selenium consumption is positively correlated with microalbuminuria in females with obesity, but not in males with obesity.